2022
DOI: 10.1021/acs.jpcc.1c10841
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic Ferromagnetism of Two-Dimensional (2D) MnO2 Revisited: A Many-Body Quantum Monte Carlo and DFT+U Study

Abstract: Monolayer MnO2 is one of the few predicted two-dimensional (2D) ferromagnets that has been experimentally synthesized and is commercially available. The Mermin–Wagner theorem states that magnetic order in a 2D material cannot persist unless magnetic anisotropy (MA) is present and perpendicular to the plane, which permits a finite critical temperature. Previous computational studies have predicted the magnetic ordering and Curie temperature of 2D MnO2 with DFT+U (Density Functional Theory + Hubbard U correction… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…28 In addition, the correct spin superexchange in the correlated cuprate Ca 2 CuO 3 has been determined 27 using DMC methods. 27 With regards to 2D materials and DMC, the band gap of GaSe 31 has been calculated to be in excellent agreement with experiment, the correct atomic structure and potential energy surface of CrI 3 39 and GeSe 30 have been predicted, and the critical temperature of MnO 2 9 has been estimated. The last step in the investigation of 2D correlated magnetic systems is the estimation of T c .…”
Section: ■ Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…28 In addition, the correct spin superexchange in the correlated cuprate Ca 2 CuO 3 has been determined 27 using DMC methods. 27 With regards to 2D materials and DMC, the band gap of GaSe 31 has been calculated to be in excellent agreement with experiment, the correct atomic structure and potential energy surface of CrI 3 39 and GeSe 30 have been predicted, and the critical temperature of MnO 2 9 has been estimated. The last step in the investigation of 2D correlated magnetic systems is the estimation of T c .…”
Section: ■ Introductionmentioning
confidence: 68%
“…DMC has the property of zero-variance, which means that as the trial wave function approaches the exact ground state (exact nodal surface), the statistical fluctuations in the energy reduce to zero . There have been reported instances where various sophisticated and expensive methods have been used to optimize the nodal surface of the trial wave function. Similar to other DMC studies of magnetic materials, ,,,,, we employed a PBE+U approach where the Hubbard U value was used as a variational parameter to optimize the nodal surface using DMC. Since we can determine the optimal U parameter variationally using DMC, it makes our final results more reliable than solely using DFT+U, where the U parameter is arbitrarily chosen or fitted to experimental data.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, their semiconducting nature does not change much with the U parameter or magnetic nature . For a pure 2D MnO 2 system, the U value was found to be between 2.4 and 3.5 eV . We have varied the U parameter from 3.0 to 5.5 eV and found that the CoMnO 4 systems remain FM and semiconducting in this range.…”
Section: Methodsmentioning
confidence: 87%
“…Because DMC has a zero-variance property, this means that as the trial wave function approaches the exact ground state, the statistical fluctuations in the energy decrease to zero . Although there have been instances in which various sophisticated methods have been used to optimize the nodal surface, we employed the PBE+ U approach, where the Hubbard ( U ) value was used as a variational parameter to optimize the nodal surface using DMC (similar to other successful DMC studies of magnetic materials ,,,, ). We performed these calculations for both T- and H-VSe 2 (24-atom supercells), where we tuned the U value from 1 to 4 eV while creating the trial wave function and computed the DMC energy.…”
mentioning
confidence: 99%